1993
DOI: 10.1002/ar.1092360214
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal development of gubernacular cones in rats and rabbits: Effect of exposure to anti‐androgens

Abstract: In male rats gubernacular cones develop during the latter half of prenatal life. Inversion of these papilla-like organs after birth is the first step to postnatal growth of the muscular cremaster sacs. The factors regulating prenatal growth and differentiation or postnatal inversion of these gubernacular cones are unknown. The lack of a detailed and unequivocal description of the normal gubernacular cone growth is judged at least partially responsible for this ignorance. The present study therefore describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
1
10
1
Order By: Relevance
“…On E17, the male gubernaculum in vivo was enlarged substantially compared with that in the female, which is in agreement with histological observations reported previ-ously (5,29,30). This difference can be explained by a difference in cell proliferation, as determined by BrdU labeling indexes.…”
Section: Discussionsupporting
confidence: 89%
“…On E17, the male gubernaculum in vivo was enlarged substantially compared with that in the female, which is in agreement with histological observations reported previ-ously (5,29,30). This difference can be explained by a difference in cell proliferation, as determined by BrdU labeling indexes.…”
Section: Discussionsupporting
confidence: 89%
“…Using scanning electron microscopy, these studies showed inhibited downward growth of the processus vaginalis in 5-day-old flutamide-treated rats. Androgens influenced the growth of the processus vaginalis and gubernacular migration at the beginning of the second phase of testicular descent [20,30]. The present study shows that blockade of androgen suppresses DNA synthesis in the gubernacular tip during the time of maximal postnatal growth (day 2).…”
Section: Discussionmentioning
confidence: 70%
“…Such a mass was noticed in the other species examined as well. In rats this structure contributes to the growth of the large (male) or small (female) inguinal cone and thus, in females, to the site of attachment of the inguinal fold of the uterine broad ligament (van der Schoot and Elger, 1993). In pigs this structure appeared the source of the temporarily observable but obvious intra-abdominal inguinal cone of young fetuses.…”
Section: C-e (Open Arrows)mentioning
confidence: 96%